The men who killed Gandhi - Malgonkar, Manohar; Kapoor, Pramod (New Delhi Lotus Collection, 2008)
On the assassination of Mahatma Gandhi, 1869-1948.
At head of title: "Illustrated with rare and unpublished documents and photographs."
Includes index.
Keywords: Gandhi, -- Mahatma, -- 1869-1948 -- Assassination; Assassins -- India; India -- Politics and government -- 1947-